Hexa cottage / Muhammad Khairi Abu Bakar ... [et al.] - Abu Bakar, Muhammad Khairi; Zulkifli, Jazmin; Zulhakem, Muhammad Hazeq; Ramli, Muhammad Afiq (2024)
The Hexa Cottage is a versatile, eco-friendly structure designed for public use, ideal for university campuses and outdoor parks. Centered around a hexagonal shape, it combines Balao or Cengal timber, acrylic, concrete, and steel for durability and sustainability. The cottage offers shelter, seating, charging, storage, and a reading area, promoting social interaction, comfort, and community engagement. Its ergonomic and adaptable design enhances the overall campus experience, supporting learning and well-being. Equipped with solar panels for emergency charging and built to withstand natural elements, the Hexa Cottage provides a harmonious and aesthetically pleasing space that integrates seamlessly with its surroundings, encouraging physical activity and environmental consciousness.